Zeocin-induced DNA damage response in barley and its dependence on ATR - Vladejić, Jovanka; Kovacik, Martin; Zwyrtková, Jana; Szurman-Zubrzycka, Miriam; Doležel, Jaroslav; Pecinka, Ales (Scientific reports, 2024)
DNA damage response (DDR) is an essential mechanism by which living organisms maintain their genomic stability. In plants, DDR is important also for normal growth and yield. Here, we explored the DDR of a temperate model crop barley (Hordeum vulgare) at the phenotypic, physiological, and transcriptomic levels. By a series of in vitro DNA damage assays using the DNA strand break (DNA-SB) inducing agent zeocin, we showed reduced root growth and expansion of the differentiated zone to the root tip. Genome-wide transcriptional profiling of barley wild-type and plants mutated in DDR signaling kinase ATAXIA TELANGIECTASIA MUTATED AND RAD3-RELATED (hvatr.g) revealed zeocin-dependent, ATR-dependent, and zeocin-dependent/ATR-independent transcriptional responses. Transcriptional changes were scored also using the newly developed catalog of 421 barley DDR genes with the phylogenetically-resolved relationships of barley SUPRESSOR OF GAMMA 1 (SOG1) and SOG1-LIKE (SGL) genes. Zeocin caused up-regulation of specific DDR factors and down-regulation of cell cycle and histone genes, mostly in an ATR-independent manner. The ATR dependency was obvious for some factors associated with DDR during DNA replication and for many genes without an obvious connection to DDR. This provided molecular insight into the response to DNA-SB induction in the large and complex barley genome.
Keywords: ječmen (rod); ATM protein; Hordeum; DNA Damage; DNA Repair; poškození DNA; bleomycin; oprava DNA; DNA; Bleomycin; Ataxia Telangiectasia Mutated Proteins